Jazia prime vendor system- a public-private partnership to improve medicine availability in Tanzania: from pilot to scale - Karin Wiedenmayer; Romuald Mbwasi; William Mfuko; Ezekiel Mpuya; James Charles; Fiona Chilunda; Denis Mbepera; Ntuli Kapologwe (Taylor & Francis Group, 2019)
Background The availability of medicines in public health facilities in Tanzania is problematic. Medicines shortages are often caused by unavailability at Medical Stores Department, the national supplier for public health facilities. During such stock-outs, districts may purchase from private suppliers. However, this procedure is intransparent, bureaucratic and uneconomic. Objectives To complement the national supply chain in case of stock-outs with a simplified, transparent and efficient procurement procedure based on a public-private partnership approach with a prime vendor at the regional level. To develop a successful pilot of a Prime Vendor system with the potential for national scale-up. Methods A public-private partnership was established engaging one private sector pharmaceutical supplier as the Prime Vendor to provide the complementary medicines needed by public health facilities in Tanzania. The Dodoma pilot region endorsed the concept involving the private sector, and procedures to procure complementary supplies from a single vendor in a pooled regional contract were developed. A supplier was tendered and contracted based on Good Procurement Practice. Pilot implementation was guided by Standard Operating Procedures, and closely monitored with performance indicators. A 12-step approach for national implementation was applied including cascade training from national to facility level. Each selected vendor signed a contract with the respective regional authority. Results In the pilot region, tracer medicines availability increased from 69% in 2014 to 94% in 2018. Prime vendor supplies are of assured quality and average prices are comparable to prices of Medical Stores Department. Procurement procedures are simplified, shortened, standardized, transparent and well-governed. Procurement capacity was enhanced at all levels of the health system. Proven successful, the Prime Vendor system pilot was rolled-out nationally, on government request, to all 26 regions of mainland Tanzania, covering 185 councils and 5381 health facilities. Conclusion The Prime Vendor system complements regular government supply through a regional contract approach. It is anchored in the structures of the regional health administration and in the decentralisation policy of the country. This partnership with the private sector facilitates procurement of additional supplies within a culture of transparency and accountability. Regional leadership, convincing pilot results and policy dialogue have led to national roll-out. Transferring this smaller-scale supply chain intervention to other regions requires country ownership and support for sustainable operations.